2013
DOI: 10.1088/0957-0233/24/9/095007
|View full text |Cite
|
Sign up to set email alerts
|

The development and characterization of a square ring shaped force transducer

Abstract: Though various types of force transducers have been developed over many years, research is continuing through the globe regarding the development of different types of force transducers. The present paper discusses the development of square ring shaped force transducers and their metrological characterization based on the calibration procedures according to standards ISO 376:2004 and IS: 4169-1988 (reaffirmed 2003). The force transducers have been developed as a modification of ring shaped force transducers an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…The uncertainty of measurement of elliptical shaped force transducer is found to be either very close or better to the uncertainty of measurement of such force transducers e.g. ring shaped force transducer (Kumar and Sharma 2012 a), hexagonal ring shaped force transducer and square ring shaped force transducer (Kumar et al 2013) are found to have uncertainty of measurement up to 0.10 (k=2), while the elliptical shaped force transducer is found to have uncertainty up to 0.10 (k=2), while taking suitable factors into account. Square ring shaped force transducer's metrological performance has not been tabulated as it has been developed only for 1 kN nominal capacity.…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…The uncertainty of measurement of elliptical shaped force transducer is found to be either very close or better to the uncertainty of measurement of such force transducers e.g. ring shaped force transducer (Kumar and Sharma 2012 a), hexagonal ring shaped force transducer and square ring shaped force transducer (Kumar et al 2013) are found to have uncertainty of measurement up to 0.10 (k=2), while the elliptical shaped force transducer is found to have uncertainty up to 0.10 (k=2), while taking suitable factors into account. Square ring shaped force transducer's metrological performance has not been tabulated as it has been developed only for 1 kN nominal capacity.…”
Section: Resultsmentioning
confidence: 66%
“…The ring shaped force transducers have been calibrated according to the standard procedure like ISO 376 and it is found that uncertainty could be about 0.025 % (excluding relative uncertainty due to hysteresis) and up to 0.10 % (including relative uncertainty due to hysteresis). Suitable discussion pertaining to different metrological characteristics has already been made by researchers (Kumar et. al., 2013).…”
Section: Analytical Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Ring shaped force transducers have been modified to square ring shaped force transducer for higher capacity [11].…”
Section: Resultsmentioning
confidence: 99%
“…The uncertainty of measurement is an indication of reliability and stability of the results reproduced by any force transducer. The uncertainty of the measurement of the force transducer has been evaluated on the basis of standard guidelines [11,12]. The sequence of the calibration procedure is as follow:…”
Section: Experimental Investigations/metrological Characterization Ofmentioning
confidence: 99%